Retrospective study to improve early initiation of breastfeeding in newborns - Jayaseelan, Joyce; Mohan, Anita Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Breast milk is the best nutrition to every new born baby. WHO recommends that all new-borns should be breastfed within one hour of birth and then on demand. Exclusive breast feeding i.e. avoiding any other feeds till 6 months of age, is best for the baby. Despite these guidelines, our national average of initiating breastfeeding within the first hour is less than 50% as per NFHS 2015-2016. The objective was to study the existing rate of early initiation of breast feeding in the study hospital. Methods: Retrospective data collection from 2015 to 2017 was used for this study. Mothers were educated about colostrum and benefits of early initiation of breastfeeding in their third trimester and during their baby shower. Results: Early initiation of breast feeding was successful among 2624 babies out of 2835 babies who were born in the study period. Conclusions: As compared to national averages, the study hospital had a superior percentage of babies being initiated early on breastfeeding. We need to educate and motivate the society to encourage exclusive breast feeding for all babies. Professional help in the form of dedicated lactation consultants of guidelines will help mothers to breast feed their babies sooner and for longer. Busting local myths and harmful practices is the need of the hour.